1998
DOI: 10.1021/np980314o
|View full text |Cite
|
Sign up to set email alerts
|

Coordinated Accumulation of (+)-δ-Cadinene Synthase mRNAs and Gossypol in Developing Seeds of Gossypium hirsutum and a New Member of the cad1 Family from G. arboreum

Abstract: A new member of the (+)-δ-cadinene synthase (CAD1) family was isolated from a Gossypium arboreum cDNA library. This cDNA encodes a protein that showed 97.3%, 96.9%, and 79.2% sequence identities with the proteins encoded by previously isolated cDNAs of cad1-C1, cad1-C14, and cad1-A, respectively. It may be grouped into the cad1-C subfamily as cad1-C2. Seeds of a glanded cotton cultivar, G. hirsutum cv. Sumian-6, were collected at different intervals during maturation, and the cad1 mRNA levels were analyzed by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
50
0

Year Published

1999
1999
2016
2016

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 55 publications
(58 citation statements)
references
References 24 publications
(68 reference statements)
8
50
0
Order By: Relevance
“…During ovule (embryo) development, biosynthesis of gossypol is tightly regulated: before 15 DPA (day post-anthesis), gossypol is undetectable; from 15-20 DPA, gossypol begin to be synthesized and then accumulated rapidly in later stages, and after 30 DPA the pigment glands containing mostly gossypol can be viewed clearly. Consistent with this, transcripts of CDN-C and CYP706B1 are also undetectable before 15 DPA, then start to accumulate at about 20 DPA and peak at about 40 DPA (Meng et al, 1999).…”
Section: Regulation Of Gossypol Biosynthesissupporting
confidence: 69%
See 2 more Smart Citations
“…During ovule (embryo) development, biosynthesis of gossypol is tightly regulated: before 15 DPA (day post-anthesis), gossypol is undetectable; from 15-20 DPA, gossypol begin to be synthesized and then accumulated rapidly in later stages, and after 30 DPA the pigment glands containing mostly gossypol can be viewed clearly. Consistent with this, transcripts of CDN-C and CYP706B1 are also undetectable before 15 DPA, then start to accumulate at about 20 DPA and peak at about 40 DPA (Meng et al, 1999).…”
Section: Regulation Of Gossypol Biosynthesissupporting
confidence: 69%
“…After multiple hydroxylation and oxidation steps, it is converted to hemigossypol and then coupled into gossypol. Several enzymes involved in this process have been isolated and characterized, including 3-hydroxy-3-methylglutaryl coenzyme A reductase (HMGR) (Joost et al, 1995), farnesyl diphosphate synthase (FPS) (Liu et al, 1999a), (+)--cadinene synthase (CDN) Chen et al, 1995;Meng et al, 1999;Tan et al, 2000), a P450 monooxygenase (CYP706B1) (Luo et al, 2001;Wang et al, 2003), P450 reductase (Yang et al, 2010), as well as a methyltransferase (Liu et al, 1999b). Recently, evidences suggest that the CYP82D109 (P450) is potentially a new gene involved in this pathway (Wagner et al, 2015) (Figure 1 B).…”
Section: Biosynthesis Of Cadinene-type Sesquiterpenoidsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, this does not exclude the possibility that GaWRKY1 may also regulate CAD1-C genes in other organs. In developing seeds, for example, genes of CAD1-A and CAD1-C showed similar temporal patterns of expression (Meng et al, 1999). Alternatively, GaWRKY1 may function as a repressor of CAD1-C genes in flower.…”
Section: Discussionmentioning
confidence: 99%
“…Formation of gossypol and related sesquiterpene aldehydes is also developmentally regulated, and these secondary metabolites accumulate in pigmented glands of aerial tissues and in epidermal and subepidermal cells of roots (Bell and Stipanovic, 1977;Halloin and Bell, 1979;Meng et al, 1999). All cotton sesquiterpene phytoalexins identified so far have a cadinene-type skeleton, and biochemical and molecular evidence has suggested that (1)-d-cadinene is the biosynthetic precursor (Chen et al, 1995;DavilaHuerta et al, 1995;Luo et al, 2001).…”
mentioning
confidence: 99%